Microstructure and mechanical properties of SKD61–Cu cooling channel fabricated via explosive welding. (September 2021) - Shin, Sang-Soo; Kim, Young-Il; Kim, Ki-Hyuk; Lee, Bin
Abstract: In this study, an explosive welding process was developed and tested to improve the cooling efficiency of a die casting mold, which was blocked on one side. After explosive welding, the microstructure and mechanical properties of the SKD61–pure Cu cylindrical molds were investigated. The stand-off distance and flyer material (Cu) thickness increased with the wave height (pocket morphology) at the interface of the sample. The shear strength also increased with the flyer material thickness and the stand-off distance. The thermal conductivity and cooling performance were also characterized, and it was revealed that the cooling effect of the SKD61 tool alloy + Cu explosive-welded sample was faster than that of the non-explosive-welded sample (approximately 15.8% of the cooling time decreased upon cooling from 270 °C to 25 °C). Data availability: The raw/processed data required to reproduce the current findings cannot be publicly available at this time as the data also forms part of an ongoing study. Graphical Abstract: ga1 Highlights: Explosive welding process was developed and tested to improve the cooling efficiency of a die casting mold(SKD61). Cooling channel of SKD61 and pure Cu bush were well bonded without intermetallic phases. The shear strength of the EW samples increased with the stand-off distance between the flying bush and mold cooling channel. The cooling efficiency of the EW sample was improved (15.8% of the cooling time decreased upon cooling from 270 ℃ to 25 ℃).